Weighted Hardy operators in local generalized Orlicz-Morrey spaces - Aykol, C.; Azizova, Z.O.; Hasanov, J.J. (Carpathian Mathematical Publications, 2021)
In this paper, we find sufficient conditions on general Young functions (Φ, Ψ) and the functions (φ_1,φ_2) ensuring that the weighted Hardy operators A_ω^α and A_ω^α are of strong type from a local generalized Orlicz-Morrey space M^0, loc_Φ, φ_1(R^n) into another local generalized Orlicz-Morrey space M^0, loc_Ψ, φ_2(R^n). We also obtain the boundedness of the commutators of A_ω^α and A_ω^α from M^0, loc_Φ, φ_1(R^n) to M^0, loc_Ψ, φ_2(R^n).